Gender-preferential language use in L1 and L2 argumentative essays? Evidence against lists of ‘gendered’ language features - Ningrum, Sulistya; Crosthwaite, Peter (Indonesian Journal of Applied Linguistics, 2020)
This study identifies and compares the gender-preferential language features present in the argumentative writing of L1 Indonesian and Indonesian L2 English learners. The data is comprised of 80 English argumentative essays sampled from the International Corpus Network of Asian Learners of English (ICNALE, Ishikawa, 2011) and a comparative corpus of 80 L1 Indonesian argumentative essays collected online from Indonesian university students, both equally divided by gender. Comparison of the data was performed through quantitative analysis of three supposed ‘male-preferential’ features and seventeen ‘female-preferential’ features between the male- and female-produced corpora in L1 and L2 writing. This study investigated (1) the extent of variation in the use of ‘gendered language features’ between male and female-produced L1 and L2 texts; (2) whether the use of male/female ‘gendered-language features’ across male/female produced L1/L2 texts match their suggested gender preference, and (3) to what extent L1’s preference for ‘gender language features’ affects male and female learners’ use of such language in L2. The results suggest the majority of supposed gender-preferential features were not significantly different across male/female produced texts, indicating that argumentative essays may be gender-neutral to a certain extent. This study also revealed that L1 preference of gendered language forms does not determine their preferences in the L2. In conclusion, male and female students adopt similar linguistic features to express their arguments. We may claim that gender language forms are not fixed and absolute in academic discourse because instructive texts tend to have a set model to fulfil the pedagogical criteria.